Synthesis of some novel 1,3,4-oxadiazole derivatives and evaluation of their antimicrobial activity - TOK, FATİH; KAYMAKÇIOĞLU, BEDİA (My University, 2022)
Treatment for microbial infections still remains an important health problem for researchers around the world. Despite a broad range of antimicrobial drugs today, there are certain obstacles associated with the use of antimicrobial agents such as drug resistance and toxicity. Thus, medicinal chemists concentrate on designing novel antimicrobial drugs. In the search for new antimicrobial agents; 1,3,4-oxadiazole compounds have come forward due to their hydrolytic stability, good chemical and thermal stability. In the scope of this work, 2-(6-chloropyridin-3-yl)-5-(substitutedphenyl)-1,3,4-oxadiazole (4a-4i) were synthesizedusing 6-chloro-N\"-(substitutedbenzoyl)nicotinohydrazide (3a-3i). These compounds were screened for their antimicrobial activities against as gram-positive bacteria S. aureus, E. faecalis, as gram-negative bacteria E. coli, P. aeruginosa, as yeast C. parapsilosis, C. albicans, C. glabrata. Among the 1,3,4-oxadiazole compounds, 4h against E. faecalis and 4b, 4f and 4g against E. coli have been found to exhibit as much as potency chloramphenicol with MIC50 values of 62.50 mu g/mL.
Keywords: Kimya; Biyokimya; Biyoinorganik Kimya; Temel Bilimler; Chemistry; Biochemistry; Bioinorganic Chemistry; Natural Sciences; KİMYA, ORGANİK; Temel Bilimler (SCI); CHEMISTRY, ORGANIC; CHEMISTRY; Natural Sciences (SCI); Chemistry (miscellaneous); Organic Chemistry; General Chemistry; Physical Sciences; Antibacterial; antifungal; infection; MIC; oxadiazole; TRANSLATION; MECHANISM; DESIGN; RING; Antibacterial; antifungal; infection; MIC; oxadiazole